Illustrated Catalogue and Type Designations of the New Zealand Zopheridae (Coleoptera: Tenebrionoidea) - Lord, Nathan P.; Leschen, Richard A.b. (Zootaxa, 2014)
This paper provides a comprehensive catalogue of the New Zealand members of the family Zopheridae Solier (Coleoptera: Tenebrionoidea) in an effort to stabilize the nomenclature preceding extensive revisionary taxonomy within the group. A checklist of the 17 New Zealand zopherid genera and an account for each of the 189 species (by current combination) is provided. Type material for nearly all species was examined, and type specimens are designated herein (90 confirmed holotypes, 3 confirmed paratypes, 102 lectotypes, 280 paralectotypes). Images of all primary type specimens and labels examined are provided. Pycnomerus sulcatissimus Sharp, 1886 is a junior synonym and secondary homonym of Pycnomerus sulcatissimus (Reitter, 1880). One replacement name is proposed, Chorasus buckleyi new name, for Chorasus subcaecus (Broun), and 23 new combinations are given.